Relationship between Stage of Chronic Kidney Disease with Cardiomegaly Imaging in Posteroanterior Chest X-Ray at Haji Adam Malik Hospital Medan - Retno, Adi; Harahap, Evo Elidar; Nasution, Bayu Rusfandi (Journal of Society Medicine, 2023)
Introduction: Chronic kidney disease (CKD) is one of the most serious health problems still faced globally. Cardiovascular complications are a major cause of morbidity and mortality in patients with chronic kidney disease. In general, cardiomegaly is found in patients with uremia which causes dysregulation of calcium and phosphate levels and increases the development of cardiovascular disease in hemodialysis patients. The aim of this study was to analyze the relationship between stages of chronic kidney disease with cardiomegaly imaging in posteroanterior  chest x-ray at H. Adam Malik Hospital Medan. Method: This study was an observational analytic study with a cross-sectional design on 78 CKD patients who underwent posteroanterior chest x-ray at H. Adam Malik Medan General Hospital from January to December 2022. Results: Of the 78 patients studied, the subjects were female (56.4%) with a mean age of 50.94 ± 12.80 years. The mean weight and BMI of the subjects were 70.49 ± 9.01 and 24.80 ± 2.82kg/m2, respectively. The mean creatinine and GFR were 7.91 ± 4.22 mg/dl and 16.08 ± 15.22 mL/min/1.73m2, respectively. The majority of subjects had creatinine >2.5 mg/dl in as many as 72 subjects (92.3%) and GFR <60 ml/min/1.73m2 as many as 62 subjects (79.4%). Most of the subjects were in CKD stage 5, as many as 59 people (75.6%). There was a positive and significant correlation between the stages of chronic kidney disease and cardiomegaly imaging in posteroanterior chest x ray with p-value <0.001. Subjects with GFR < 60 mL/min/1.73m2 and overweight BMI status (25.0 - 29.9 kg/m2) had a greater risk factor for cardiomegaly. Conclusion: There is a positive and significant correlation between the stages of chronic kidney disease with cardiomegaly imaging in posteroanterior chest x-ray at H.Adam Malik General Hospital Medan with p value <0.001.